Resistência à flexão de espigões de fibra de vidro após esterilização por 2 métodos distintos - Rui Canelas (2014)
Objective: To determine whether autoclave sterilization or a high-level disinfectant can affectthe properties of the original glass fiber post, particularly regarding its resistance to fractureby bending.Methods: Twenty-four fiber glass posts were used, divided into three groups. The first group,named control group, consisting of eight elements; the second group, autoclavegroup, consisted of eight posts submitted to autoclave sterilization. The third andfinal group, disinfectant group, was made of eight posts immersed on a high-level disinfectantsolution. After the process of sterilization/disinfection the resistance to fracture by bendingwas analyzed, using the three-point bending test. To verify ifthere were any differencesbetween at least two groups, the parametric One-way ANOVA test was used. The Bonferronitest was used to verify between which groups there were significant statistical differences.Results: It was found that the autoclave group and the control group had significant statisticaldifferences (p < 0.001). The same was observed between the disinfectant and the controlgroup (p = 0.002). At a 95% confidence level, no significant statistical differences were foundbetween the autoclave and disinfectant groups (p = 0.829).Conclusions: The sterilization/disinfection procedures diminished the fiber post resistance,leading to a bigger chance of fracture when compared to the control group.e o grupo dos espigões esterilizados em autoclave (p < 0,001) e entre o grupo controlo e ogrupo desinfetante (p = 0,002). Não foram verificadas diferenças com significado estatístico,para um intervalo de confianca de 95%, entre os grupos dos espigões submetidos a autoclavee ao desinfetante (p = 0,829).Conclusões: A resistência à fratura por flexão diminuiu nos espigões submetidos quer aesterilizaçãoo com autoclave quer a desinfeção com um desinfetante de alto nível.